Assessment of Knowledge, Attitude, and Practice in Respect of Medical Waste Management among Healthcare Workers in Al-Imammein Al-Kadhimein Teaching Hospital - Dalia Riadh Ali Adulrahman; Yasir Mahmood Jawad; Reem Jameel Hasan Al-Haidary (International Journal of Health and Medicine, 2025)
Waste that arises from health care activities, including diagnosing, preventing, and treating diseases, is known as Medical waste, and it poses threats to human and environmental health if adequately addressed. Objectives: This study aimed to identify HCWs' knowledge, attitude, and practice concerning MWM at Al-Imammein Al-Kadhimein Teaching Hospital in Iraq. Patients and methods: An exploratory quantitative descriptive survey was administered to 300 randomly selected healthcare personnel and included questions on knowledge, attitude, and practice about MWM. Results: All statistical analysis was done using SPSS-25 with significance testing done at p-value ≤ 0.05 using the Pearson Chi-square test (X2-test). The cross-tabulation analysis by percentage showed that 55.7% of respondents had good knowledge, 25.3% had moderate knowledge, and 19% had poor knowledge of MWM. In this case, the positive attitude of the participants was 57. 7%, while the negative attitude was 42.3%. While comparing the practices, 46.7% followed good practices, and 53.3% followed poor practices.Conclusions: Overall knowledge, attitude, and practice regarding medical waste management showed average responses from the included participants, necessitating implication for training programs to raise the healthcare personnel's knowledge.